Design, syntheses, and crystal engineering of versatile supramolecular reagents - Urbina, Joaquin Francis (Kansas State University, 2005)
Crystal engineering, or non-covalent synthesis in the solid state, requires an understanding of intermolecular forces, and the hydrogen bond has become a reliable non-covalent tool in the construction of supramolecular architectures. In the same way that synthetic chemists refer to a “yield” to quantify a desired product, crystal engineers typically determine the successful formation of a supramolecular product according to the frequency or occurrence of preferred intermolecular interactions between molecules under certain reaction conditions, thus, the supramolecular yield. These non-covalent reactions can be effectively carried out using supramolecular reagents (SR’s). A family of ditopic bis-imidazol-1-yl/benzimidazol-1-yl compounds were synthesized and used as SR’s in combination with a variety of dicarboxylic acids to produce binary solids in 100% yield through the primary acid···imidazol-1-yl/benzimidazol-1-yl synthons even in the presence of potentially disruptive intermolecular interactions. We furthermore noted that secondary C–H···O interactions within and between 1-D chains were of equal structural importance based upon an analysis of the metrics displayed by these interactions. The use of these SR’s as ligands with neutrally charged metal complexes was also investigated. SR’s containing benzimidazol-1-yl and carboxamide moieties were synthesized and combined with two different carboxylic acids to make ternary solids through acid···benzimidazol-1-yl and carboxamide···acid hydrogen bonds using a hierarchical approach – the best donor-best acceptor, second best donor-second best acceptor guidelines. These SR’s were also employed as ligands for high-yielding syntheses of linear metal complexes where neighboring complexes are linked via carboxamide···carboxamide hydrogen bonds. Asymmetric SR’s possessing two different N-heterocycles were synthesized and employed in the construction of ternary supermolecules with a high degree of structural selectivity and specificity when introduced to two different carboxylic acids. The stronger acid interacts at the more basic site, while the weaker acid hydrogen-bonds with the less basic nitrogen atom. Finally, an SR containing three different binding sites was designed and synthesized with the aim of producing quaternary co-crystals.
Keywords: Crystal engineering; Hydrogen bonds; Supramolecular chemistry; Supramolecular yield; Supramolecular reagents; General chemistry (0485)